Fundamentals of managerial finance - Neveu, Raymond P. (Cincinnati : South-Western Publishing, Co., 1985)
This book was designed and written for use in fundamental managerial finance courses. The first edition was used primarily in the first finance course taken by undergraduate business majors and in MBA programs that provide background courses for those students who have no prior exposure to managerial finance. In addition, portions of these materials have been used in executive development seminars. This second edition is intended for the same courses. My goal in writing this book was to produce a managerial finance text that students would find both readable and understandable and that instructors would find teachable. Classroom use, student evaluations, and adopter comments have confirmed the attainment of this goal. Thus, when the time came to revise the manuscript, careful attention was paid to maintaining these desirable qualities in preparing chapter revisions; in addition, new chapters were designed, written, class tested, and revised with these qualities in mind.
Part 1. Introduction -- Part 2. Financial Analysis -- Part 3. Working Capital Management -- Part 4. Capital Building -- Part 5. Valuation, Cost capital, and Capital structure -- Part 6. Capital Asset pricing and managerial finance -- Part 7. Long term financing -- Part 8. Special topics in management finance.
Includes index.
Keywords: FINANCE